261Can a physical activity supportive environment reduce socioeconomic inequities in incident coronary heart disease?. (2nd September 2021) - Gullon, Pedro; Bilal, Usama; Hirsch, Jana A.; Rundle, Andrew; Judd, Suzanne; Safford, Monika; Lovasi, Gina S.
Abstract: Background: This research aims to: (1) explore the contribution of physical activity supportive environments to income inequities in coronary heart disease (CHD) incidence, and (2) investigate whether income inequities in CHD incidence are modified by physical activity supportive environments. Methods: We used data from the REGARDS study, which recruited US-residents aged 45 or older between 2003 and 2007. Our analyses included participants at risk for incident CHD (n = 20808), followed until December 31 st 2014. We categorized household income and treated it as ordinal: (1) $75, 000+, (2) $35, 000-$74, 000, (3) $20, 000-$34, 000, and (4) <$20, 000. We operationalized physical activity supportive environments within a 1-km residential buffer as density of walkable destinations and physical activity facilities, and proportion green land cover. Cox models were estimated the adjusted association of income with incident CHD, and tested effect modification by environment variables. Results: We found a 17% (95% CI 8% to 25%) increased hazard of CHD per decrease in household income category. After adjusting for physical activity environments, the HR was attenuated by 3% (HR = 1.15), and the income-CHD association was stronger in areas lacking walking destinations (HR = 1.54 vs 1.16). Conclusions: Physical activity supportive environments, especially those with walking destinations, may moderate associations between household income and CHD. Key messages: Low-income individuals have greater risk of developing CHD, however, the built environment has a small moderating effect on this association. Income inequities in CHD were also noted to be higher in areas with no walking destinations